KAJIAN KUALITAS HABITAT DAN TINGKAT KEPADATAN MONYET HITAM SULAWESI (Macaca nigra) DI KESATUAN PENGELOLAAN HUTAN KONSERVASI (KPHK) TANGKOKO SULAWESI UTARA - Dwi Yandhi Febriyanti; Hengki Johannis Kiroh; Saroyo ., nfn (AGRI-SOSIOEKONOMI, 2019)
This study aims to (1) evaluate the habitat quality of Black crested macaque at The Tangkoko Conservation Forest Management Unit, (2) analyze the population density level of Black crested macaque at The Tangkoko Conservation Forest Management Unit, (3) analyze the corelation between habitat quality and Black crested macaque density at The Tangkoko Conservation Forest Management Unit. The study was conducted from July to October 2017 in the Tangkoko Conservation Forest Management Unit, North Sulawesi. The material observed was the Black crested macaque and their habitat. The data collection method used is habitat quality data collection carried out by making sample plots measuring 25 m x 25 m for tree level observations in lanes with each distance between sample plots is 250 m. Data recorded for extraction and dominance of vegetation are species names, number of individuals and breast diameter at breast height. data collection on the density of Black crested macaque is done by way of inventorying animals directly through surveys in the field. Observations are carried out by walking at speeds of 1 - 1.5 km / h on each track and stopping at every 100 m to hear and observe the surroundings.Observations are carried out in the morning (6:00 - 11:00) and in the afternoon (14:00 - 17:00). Data recorded is the number of individuals found using the line transect method. Data analysis used (1) Important value index (INP) is a quantitative parameter that can be used to express the level of dominance (level of mastery) of species in the tree community. (2) Analysis of individual density is carried out according to the meeting of individuals in the group during observation (3) Parametric statistical tests ofPearson correlation. The results showed that (1) habitat quality parameters analyzed were important value index with the highest value of 95.63% in Cananga odorata on line A1; (2) the population density level of Black crested macaque was 9.66 individuals / km2. The highest amount of density is found on the T1 line where the T1 line is located in the Batuputih Tourism Park which routinely gets tourist visits. There are two pathways that are not found in the Black crested macaque namely T10 and A2 lines; (3) Based on the Pearson correlation analysis showed that the correlation between habitat quality and density of Black crested macaque that shows a positive value.*eprm*